Potensi Kitosan sebagai Edible Coating pada Buah Anggur Hijau (Vitis vinifera Linn) - Hilma Hilma; Ahmad Fatoni; Dwi Puspita Sari (Faculty of Mathtmatics and Natural Sciences, 2018)
A study has been conducted on influences of various chitosan concentrationas coating and storage time to Vitamin C concentration of green grape (Vitis vinifera L.) by dipping method. This study aims to de-termine the difference of chitosan concentration to physical characteristics, weight loss and vitamin C concen-tration of green grape. Chitosan coating was conducted on 50 grams of green grape by dipping method at var-ious concentration of chitosan that is 0%, 0,5%, 1%, 1,5% and 2% (w / v), kept on variation of one, four and seven day storage time. Determination of vitamin C concentration of green grape was done by UV-Vis spec-trophotometer measured at 256 nm wavelength with regression equation y = 0,0344 x + 0,101 and r = 0,998. Based on statistical test showed that chitosan concentration of 1% (w / v) with 4 days storage time is the most optimum because the chitosan layer is able to close all green grape pores, so the process of anaerobic and CO2 respiration can be inhibited by chitosan solution.